The plant immunity inducer pipecolic acid accumulates in the xylem sap and leaves of soybean seedlings following Fusarium virguliforme infection - Abeysekara, Nilwala S (Plant science : an international journal of experimental plant biology, 2016)
Copyright © 2015 Elsevier Ireland Ltd. All rights reserved.